Control system for automation of technical and economic calculations at the enterprise - Kobielieva, T. O.; Pererva, P. G.; Ponomarev, V. D. (Видавничий дім "Києво-Могилянська академія", 2023)
The formation of a specific management structure, taking into account all types of hierarchy, is determined by the specifics of the enterprise, its functional, informational and target features. The used hierarchical approach of the enterprise management system can be presented in the form of a functional model of the management process, which can consist of various mathematical models describing the real and necessary state of the object, and criteria for the optimality of the management object.
Система управління автоматизацією техніко-економічних розрахунків на підприємстві
Keywords: automation; technical and economic calculations; information technologies; efficiency; production